Work-Life Balance, Job Stress and Employee Engagement on Employee Job Satisfaction - Salsabila, Haika; Yasmin, Devi (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to investigate the influence of Work-life Balance, Job Stress, and Employee Engagement on employee job satisfaction at PT Bumi Pratama Khatulistiwa, Kubu Raya Regency. This study uses an associative research design. The population consists of all factory employees of PT Bumi Pratama Khatulistiwa, totaling 123 people. The sampling method used is saturated sampling. The analytical tools used include multiple linear regression, correlation coefficient, coefficient of determination, simultaneous test (F test), and partial test (t test). Work-life Balance, Job Stress, and Employee Engagement together have a significant influence on Job Satisfaction. Work-life Balance affects Job Satisfaction partially, as well as Job Stress and Employee Engagement. This study makes a novel contribution by exploring the impact of Work-life Balance, Job Stress, and Employee Engagement on Job Satisfaction in the context of the oil palm plantation industry. The findings provide valuable insights for the management of PT Bumi Pratama Khatulistiwa to improve employee job satisfaction, by assisting in the development of more effective policies.